CONFERENCES AND SYMPOSIA : Spatio-temporal shaping of photocathode laser pulses for linear electron accelerators. (2nd January 2018) - Mironov, S Yu; Andrianov, A V; Gacheva, E I; Zelenogorskii, V V; Potemkin, A K; Khazanov, E A; Boonpornprasert, P; Gross, M; Good, J; Isaev, I; Kalantaryan, D; Kozak, T; et al.
Abstract: Methods for the spatio-temporal shaping of photocathode laser pulses for generating high brightness electron beams in modern linear accelerators are discussed. The possibility of forming triangular laser pulses and quasi-ellipsoidal structures is analyzed. The proposed setup for generating shaped laser pulses was realised at the Institute of Applied Physics (IAP) of the Russian Academy of Sciences (RAS). Currently, a prototype of the pulse-shaping laser system is installed at the Photo Injector Test facility at DESY, Zeuthen site (PITZ). Preliminary experiments on electron beam generation using ultraviolet laser pulses from this system were carried out at PITZ, in which electron bunches with a 0.5-nC charge and a transverse normalized emittance of 1.1 mm mrad were obtained. A new scheme for the three-dimensional shaping of laser beams using a volume Bragg profiled grating is proposed at IAP RAS and is currently being tested for further electron beam generation experiments at the PITZ photoinjector.